Outdoor Learning for Cadets of Maritime Higher Education Institute: The Students' Perspective - Purnama Nancy Lumban Batu; Wida Cahyaningrum (Biormatika : Jurnal ilmiah fakultas keguruan dan ilmu pendidikan, 2020)
This paper aims to describe how motivation, attitude, input, and exposure affect learners anxiety in students uptake in acquiring English. The participants of this study are adult learners who have learned English averagely for more than ten years. Studies on SLA have illustrated that learners' anxiety could hinder them from acquiring a second or a foreign language. As an effort to reduce the tension and anxiety, a set of out-of-classroom learning activities was conducted. It was then observed how the students gradually loosened their anxiety and gained more confidence in expressing themselves in English throughout the activities